Tribolium castaneum HERBST (Coleoptera: Tenebrionidae) AS a toxicity model for the study of volatile chemicals (2018)
Humans are exposed to thousands of chemical substances, therefore, the responses of these toxic substances and their interactions with environmental factors can occur at various time scales and at different levels of biological complexity. Currently, there are more than five million man-made chemicals and the number of new products that appear annually has increased enormously, generating a growing gap between the evaluation capacity and the need of new toxicity detection tools. In vivo studies are used to determine different levels of toxicity; however, these tests can be very expensive, consume more time and use a large number of animals. Therefore, it is necessary to develop new models for the evaluation of toxicity based on the principles 3R - Reduce, Replace, Refine. Invertebrate organisms have an easy and economical maintenance, a short life cycle, small size, simple anatomy and are extremely useful to provide an early and sensitive detection of toxicity, as well as a better understanding of the biochemical mechanisms involved, allowing a more predictable of the toxicity of unknown compounds. In addition, a large number of invertebrates can be studied in a single experiment within a short period of time, with fewer ethical problems and its maintenance cost is lower compared to other animals. Tribolium castaneum, is a model organism for agricultural and medical research, some authors consider it a better representative of the Insecta class than Drosophila melanogaster. In view of the need for new toxicity models, this work aimed to propose the T. castaneum insect as a toxicity model for the study of volatile chemicals of natural and synthetic origin, evaluating the molecular mechanisms involved. Based on the above, the work contemplates four phases, described below. In the first, the development of the insect in laboratory conditions and its life cycle was evaluated. In the second, the effects of benzene, naphthalene, toluene, xylene, and thinner are studied in several genetic markers of toxicity on the red flour beetle, using the polymerase chain reaction (PCR) in real time, and the lethal concentration 50 (LC50) of each chemical was determined. In addition, gas chromatography coupled to mass spectrometry was used to identify the compounds present in the thinner and the naphthalin balls. The third phase, evaluates three toxicological endpoints (development, growth, and reproduction) in the Coleoptera exposed to eight toxic chemicals. Finally, the expression of genes related to neurotransmission in T. castaneum exposed to linalool and β-pinene was studied, using real-time PCR, in addition the repellent concentration 50 (RC50) was determined and in silico interaction with important proteins for the insect was evaluated. The results obtained show that the development cycle of the immature stages of the insect is in the range of 46-81 days. The egg stage has a duration of 6-7 days, and a size of 0.6 ± 0.0 x 0.3 ± 0.0 mm, the larvae can reach up to eight instars and can go to the pupal stage from the fourth instar. The pupa stage lasts 7 ± 1.7 days and a size of 3 ± 0.1 x 1.1 ± 0.0 mm. Adults have a size of 3.6 ± 0.0 x 1.1 ± 0.0? mm. The LC50 for naphthalene, naphthalin and benzene was 63.6, 20.0 and 115.9 μL/L in air, respectively. Naphthalin balls mainly contained naphthalene and in a lesser proportion benzo[b]thiophene. Real-time PCR analysis revealed changes in the expression of genes related to oxidative stress, metabolism, reproduction, metamorphosis, and neurotransmission in naphthalene-exposed insects. Adults exposed to benzene overexpressed genes related to neurotransmission, reproduction, metamorphosis and development. The main compounds identified in the thinner with peak area > 2% were p-xylene (6.00%), toluene (3.98%), 2,4-dimethylheptane (2.99%), methylcyclohexane, (2.75%), 2-methylheptane, (2.04%), cyclohexanone (2.58%) and nonane (2.10%). Xylene was highly toxic and most animals did not survive 4 hours of exposure. The LC50 values for toluene, xylene and thiner at 48 h of exposure were 97.7, <40.0 and 99.8 μL/L of air, respectively. The gene expression of glutathione-S-transferase increased after exposure to thiner and toluene. Expression of the superoxide dismutase gene increased after exposure to toluene. On the other hand, the effect observed at the level of reproduction and development after exposure to eight chemical compounds was abnormalities in the stages of larva and pupa induced by bisphenol A and mercury (II) chloride, while phenol, toluene and metronidazole, showed an effect on the pupa stage. Hydroquinone and hydrazine hydrochloride affected the weight of the larva and pupa, respectively. The main anomalies observed were necrosis in appendages of larvae, in pupae the absence of papillae for sexual differentiation and abnormality in the formation of head, extremities, wings and appendages. Studies with two components of natural origin, indicated that β-pinene was more potent than linalool to induce insect repellency, with RC50 values of 0.03 and 0.11 μL / cm2, respectively. Both compounds induced overexpression of the Hiscl2 gene in adult insects, and β-pinene promoted overexpression of the Grd and Ace1 gene. However, these monoterpenes had little potential for coupling in computer-generated models for several important proteins in the neurotransmission of T. castaneum since their respective binding affinities were marginal, and therefore the repellent action probably involved mechanisms other than the interaction direct with these protein targets. In summary, with the obtained results it is demonstrated that the T. castaneum insect can be used as a toxicological model for the study of volatile compounds, the effects are quantitatively measurable at the level of gene expression, development, growth, reproduction, and mortality